Facial Emotion Recognition and Polymorphisms of Dopaminergic Pathway Genes in Children with ASD - Zhuo Liu; Jun Liu; Zengyu Zhang; Hong Yu; Fengpei Hu (Behavioural Neurology)
Background. It is inconclusive whether children with autism spectrum disorder (ASD) experience a deficit in facial emotion recognition. The dopaminergic pathway has been implicated in the pathogenesis of ASD. This study was aimed at determining facial emotion recognition and its correlation with polymorphisms in the dopaminergic pathway genes in children with ASD. Methods. Facial emotion recognition was examined in 98 children with ASD and 60 age- and gender-matched healthy controls. The severity of ASD was evaluated using the Childhood Autism Rating Scale (CARS). DNA from blood cells was used to analyze the genotypes of single-nucleotide polymorphisms (SNPs) in dopaminergic pathway genes. SNPs of DBH rs1611115, DDC rs6592961, DRD1 rs251937, DRD2 rs4630328, and DRD3 rs167771 were analyzed. Results. Children with ASD took a significantly longer time to recognize all facial emotions, and their interpretations were less accurate for anger at low intensity and fear at both low and high intensities. The severity of the disease was associated with significant delays in recognition of all facial emotions and with a decrease in accuracy in recognition of happiness and anger at low intensity. Accuracy in recognizing fear at high intensity and sadness at low intensity was associated with rs251937 and rs4630328, respectively, in children with ASD. Multivariate logistic regression analysis revealed that SNP rs167771, response time for the recognition of happiness, sadness and fear, and accuracy in recognition of anger and fear were all associated with the risk of childhood ASD. Conclusions. Children with ASD experience a deficit in facial emotion recognition. Certain SNPs in the dopaminergic pathway genes are associated with accuracy in recognizing selective facial emotions in children with ASD.